Morpho-Physiological, Yield, and Transgenerational Seed Germination Responses of Soybean to Temperature - Alsajri, Firas Ahmed; Wijewardana, Chathurika; Bheemanahalli, Raju; Irby, J. Trenton; Krutz, Jason; Golden, Bobby; Reddy, Vangimalla R.; Reddy, K. Raja (Frontiers in Plant Science, 2022)
Temperature is the primary factor affecting the morpho-physiological, developmental, and yield attributes of soybean. Despite several temperature and soybean studies, functional relationships between temperature and soybean physiology and yield components are limited. An experiment was conducted to determine temperature optimum for soybean gas exchange and yield components using indeterminate growth habit cultivar (Asgrow AG5332, AG) and determinate cultivar (Progeny P5333 RY, PR). Plants grown outdoors were exposed to five day/night temperature treatments, 21/13, 25/17, 29/21, 33/25, and 37/29°C, from flowering to maturity using the sunlit plant growth chambers. Significant temperature and cultivar differences were recorded among all measured parameters. Gas exchange parameters declined with increasing temperature treatments during the mid-pod filling stage, and quadratic functions best described the response. The optimum temperature for soybean pod weight, number, and seed number was higher for AG than PR, indicating greater high-temperature tolerance. Soybean exposed to warmer parental temperature (37/29°C) during pod filling decreased significantly transgenerational seed germination when incubated at 18, 28, and 38°C. Our findings suggest that the impact of temperature during soybean development is transferable. The warmer temperature has adverse transgenerational effects on seed germination ability. Thus, developing soybean genotypes tolerant to high temperatures will help growers to produce high-yielding and quality beans. The quantified temperature and soybean physiology and yield components-dependent functional algorithms would be helpful to develop adaptation strategies to offset the impacts of extreme temperature events associated with future climate change.